Performance analysis of soil-geopolymer deep mix column in soft soil under static and cyclic loading - Gupta S.; Kumar S.; Pradeep N.M.; Nishant M. (My University, 2025)
Deep soil mixing (DSM) is a widely used ground improvement method to enhance the properties of soft soils by blending them with cementitious materials to reduce settlement and form a load-bearing column within the soil. However, using cement as a binding material significantly contributes to global warming and climatic change. Moreover, there is a need to understand the dynamic behavior of the DSM-stabilized soil under traffic loading conditions. In order to address both of the difficulties, a set of 1-g physical model tests have been conducted to examine the behavior of a single geopolymer-stabilized soil column (GPSC) as a DSM column in soft soil ground treatment under static and cyclic loading. Static loading model tests were performed on the end-bearing (l/h = 1) GPSC stabilized ground with Ar of 9 %, 16 %, 25 %, and 36 % and floating GPSC stabilized ground with l/h ratio of 0.35, 0.5, and 0.75 to understand the load settlement behavior of the model ground. Under cyclic loading, the effect of Ar in end-bearing conditions and cyclic loading amplitude with different CSR was performed. Earth pressure cells were used to measure the stress distribution in the GPSC and the surrounding soil in terms of stress concentration ratio, and pore pressure transducers were used to monitor the excess pore water pressure dissipated in the surrounding soil of the GPSC during static and cyclic loading. The experimental results show that the bearing improvement ratio was 2.28, 3.74, 7.67, and 9.24 for Ar of 9 %, 16 %, 25 %, and 36 %, respectively, and was 1.49, 1.82, and 2.82 for l/h ratios of 0.35, 0.5, and 0.75 respectively. Also, the settlement induced due to cyclic loading was high under the same static and cyclic stress for all the area replacement ratios. Furthermore, the impact of cyclic loading is reduced with an increase in the area replacement ratio. Excess pore water pressure generated from static and cyclic loads was effectively decreased by installing GPSC. © 2025 Elsevier Ltd